2016
DOI: 10.1002/ange.201601788
|View full text |Cite
|
Sign up to set email alerts
|

Pressure‐Dependent Polymorphism and Band‐Gap Tuning of Methylammonium Lead Iodide Perovskite

Abstract: We report the pressure‐induced crystallographic transitions and optical behavior of MAPbI3 (MA=methylammonium) using in situ synchrotron X‐ray diffraction and laser‐excited photoluminescence spectroscopy, supported by density functional theory (DFT) calculations using the hybrid functional B3PW91 with spin‐orbit coupling. The tetragonal polymorph determined at ambient pressure transforms to a ReO3‐type cubic phase at 0.3 GPa. Upon continuous compression to 2.7 GPa this cubic polymorph converts into a putative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 38 publications
4
53
0
Order By: Relevance
“…34 The band gap narrows under <1 GPa hydrostatic compression due to increasing in antibonding overlap of Pb-X; on the contrary, the band gap broadens under high pressure (>1 GPa), which could be due to phase change or amorphization in the high-pressure regime. 29 Hall et al also observed a blue shift of photoluminescence (PL) of CH3NH3PbI3 in the presence of humidity, and their first-principles computation shows a simultaneous increase of lattice constant and band gap when intercalating water into the lattice, 35 suggesting that the band gap may be tunable by straining the crystal lattice. Along similar lines, researchers have recently demonstrated an increase in band gap with epitaxial growth of CsPbBr3 on VO2 nanowires, which results from compressive in-plane strains in the CsPbBr3 during expansion of the nanowires.…”
Section: Introductionmentioning
confidence: 99%
“…34 The band gap narrows under <1 GPa hydrostatic compression due to increasing in antibonding overlap of Pb-X; on the contrary, the band gap broadens under high pressure (>1 GPa), which could be due to phase change or amorphization in the high-pressure regime. 29 Hall et al also observed a blue shift of photoluminescence (PL) of CH3NH3PbI3 in the presence of humidity, and their first-principles computation shows a simultaneous increase of lattice constant and band gap when intercalating water into the lattice, 35 suggesting that the band gap may be tunable by straining the crystal lattice. Along similar lines, researchers have recently demonstrated an increase in band gap with epitaxial growth of CsPbBr3 on VO2 nanowires, which results from compressive in-plane strains in the CsPbBr3 during expansion of the nanowires.…”
Section: Introductionmentioning
confidence: 99%
“…(GA)(MA) 2 Pb 2 I 7 (GA = guanidinium) and (MA)(BA) 2 Pb 2 I 7 (BA = butylammonium) also only achieve maximal ∼5and ∼3.5-fold of enhancements within 1-2 GPa, respectively. Nonetheless, as pressure further increased to ∼6 and ∼1.75 Gpa, (3AMP)PbI 4 and (3AMP)(MA) 3 Pb 4 I 13 , respectively, appeared to exhibit decreased PL intensities, which is associated with the partial amorphization of their lattices (32)(33)(34).…”
Section: Significancementioning
confidence: 97%
“…S14-S16). This pressuredriven order-disorder transition is a general phenomenon for organic-inorganic perovskite materials (31,32,38). Now, we consider the anisotropic compression behavior of the D-J perovskites.…”
Section: Significancementioning
confidence: 99%
“…To this end, surfactant-assisted self-assembly strategy can achieve more compact film configuration for stronger electronic coupling and charge mobility by building high-quality self-assembled QD films and reducing interparticle spacing among QDs. Recently, direct assembly such as stress-induced assembly has been developed to tune NP phase transformation and coupling (Jiang et al., 2016, Quan et al., 2011, Quan et al., 2013, Wang et al., 2015, Nagaoka et al., 2017, Zhu et al., 2017). It also requires ordered NP assemblies as the starting materials to accomplish the stress-induced tuning of phase transition and interparticle separation.…”
Section: Applicationsmentioning
confidence: 99%